Margin and Marketing Efficiency of Salted Fish of Parigi Hamlet Central Maluku Regency - Yolanda M.T.N. Apituley; Risky; Hellen Nanlohy (School of Business, IPB University (SB-IPB), 2024)
Background: Salted fish have been preserved by salting and are very well known to the Indonesian people. Apart from being affordable, salted fish is also easy to obtain. Salted fish production is generally in coastal areas and distributed to distant places. Therefore, it is urgent to analyze the distribution process and the efficiency of that process.Purpose: This research aims to determine marketing channels and analyze the margin and marketing efficiency of salted fish produced in Parigi Hamlet, North Seram District, Maluku Regency.Design/methodology/approach: The primary research method used is the descriptive method, where sampling is carried out using exhausting sampling and snowball sampling. The data was analysed by using descriptive qualitative and descriptive quantitative.Findings/Results: The distribution of salted fish products produced in Parigi Hamlet consists of three channels, namely (1) processor – consumer, (2) processor – retailer – consumer, and (3) processor – collector – retailer – consumer. The marketing margin on channel-1 is Rp 0,- channel-2 is Rp 20,000,- and channel-3 is Rp 30,000.- Marketing channel-1 has an efficiency value of 0.07%, marketing channel-3 is 2.46%, and channel-2 is 2.52%.Conclusions: All three marketing chains are efficient, but the most efficient is channel 1 because there are no intermediary institutions, and the costs incurred are lower than others.Oiginality/value (State of the art): Even though marketing channel-1 is the most efficient, the number of products sold is small. Processors prefer marketing channel-3 because collectors usually buy in large quantities. Keywords: salted fish, marketing margin, efficiency.